A EVALUASI KINERJA CWDM 8 CHANNEL DENGAN VARIASI PANJANG GELOMBANG: FOKUS POWER LINK BUDGET, SNR DAN BER - Rojabi, Alpiyan Arif; Fauzi, Ahmad; Putri, Dewi Indriati Hadi (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2024)
The need for internet connection continues to grow and is the main priority of the Indonesian population. The use of fiber optic as a transmission system aims to increase data transfer speed and is resistant to interference. The use of CWDM technology can overcome high traffic volumes by dividing the wavelength. PT. Surya Citra Media has a network that connects the SCTV tower office with the IVM office in Daan Mogot. This study examines the performance of the CWDM fiber optic network link SCTV Tower - IVM Daan Mogot. The CWDM used has a capacity of 8 channels with a wavelength of 1310nm to 1450nm with a channel spacing of 20nm. This study was conducted to evaluate the 8-channel CWDM fiber optic network through performance measurements. The performance of the fiber optic network is focused on the parameters of the power link budget, SNR and BER. The results showed a power link budget of -9.407 dB and an SNR value with the smallest value of 37.0864 and the largest of 37.6150 dB. While the BER value ranges from 10-10 to 10-11. So that the network can be declared feasible based on the evaluation results.